Blood Flow Turbulence Quantification of Carotid Artery With a High‐Frame Rate Vector Flow Imaging. (18th June 2022) - Dong, Yinghui; Hong, Shaofu; Song, Di; Liu, Mengmeng; Gao, Wenjing; Du, Yigang; Xu, Jinfeng; Dong, Fajin
Abstract : Objectives: To assess the feasibility and performance of Turbulence (Tur) index as a quantitative tool for carotid artery flow turbulence; to detect and compare the blood flow patterns of common carotid artery (CCA) and carotid bulb (CB) at different ages and cardiac phases in healthy adults, and thus interpret the evolvement of etiology difference between CCA and CB. Methods: Carotid flow characteristics of 40 healthy volunteers were evaluated quantitatively by a high‐frame rate vector flow imaging. Three types of flow patterns were defined depending on the distributive range of complex flow during systole in CB. Comparison of mean Tur value in CCA and CB at different age groups and cardiac phases was performed. And the correlation between Tur value and the diameter ratio of proximal internal carotid artery to common carotid artery (DRpro‐ica/cca) was tested. Results: Mean Tur values in CB were remarkably higher than that in CCA, whether during systole or diastole ( P < .001). Meanwhile Tur values in CB during systole were significantly higher than that during diastole ( P < .001). Flow complexity of CB showed variations among 40 participants especially in systole, whereas the flow pattern of CCA was relatively consistent. Mean Tur values were positively correlated with DRpro‐ica/cca in CB ( ρ = 0.69, P < .05). Conclusions: V Flow imaging provided a reliable method—Tur, for quantitative analysis of carotid blood flow. It had potential to be further applied in distinguishing complex hemodynamic characteristics in high‐risk people of carotid diseases for the risk stratification of cardiovascular events.